Financial modeling using quantum computing : a complete guide on how to design and manage quantum computing solutions in financial analysis /: a complete guide on how to design and manage quantum computing solutions in financial analysis. (2023) - Saxena, Anshul; Mancilla, Javier; Hussain, Shadab; Montalban, Iraitz
No abstract available